2017
DOI: 10.1097/nur.0000000000000335
|View full text |Cite
|
Sign up to set email alerts
|

Process of Transition for Congenital Heart Patients

Abstract: A nurse-led transition clinic enhances long-term care of patients by supporting the young adults and their family/carer through the transition and transfer of the care to promote the young adult's understanding of their condition and to prevent any lost to follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…They can be pivotal in the role of transition coordinator [21,25,31,32]. In line with our results, examples of transition programmes in the literature J o u r n a l P r e -p r o o f showed that such nurses in this role as transition coordinator offer individualised and structured support, guidance, and education to patients and parents [14][15][16]33]. Our survey also showed that some transition criteria regarding this aspect were met less frequently.…”
Section: Transfer and Transition Criteriasupporting
confidence: 84%
“…They can be pivotal in the role of transition coordinator [21,25,31,32]. In line with our results, examples of transition programmes in the literature J o u r n a l P r e -p r o o f showed that such nurses in this role as transition coordinator offer individualised and structured support, guidance, and education to patients and parents [14][15][16]33]. Our survey also showed that some transition criteria regarding this aspect were met less frequently.…”
Section: Transfer and Transition Criteriasupporting
confidence: 84%
“…The involvement of a nurse in the transition clinic (multidisciplinary team), with the aim of spending time in helping CHD adolescents develop a comprehensive understanding of their condition, self-care management, and the skills that are needed to take part in adult life is another reliable strategy to prevent any lapse in care [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Educational components were coded based on topics that aimed to assess, provide, or increase participants' knowledge about their diagnosis and health management (n=9, 90%). Patient teaching activities included a one-on-one nurse led educational session between specifically trained cardiology nurses and adolescents within an inpatient or transitional clinic settings (n=4, 40%) (Acuña Mora et al, 2017, 2020Habibi et al, 2017;Ladouceur et al, 2017;Mackie et al, 2014Mackie et al, , 2016. Other activities included the use of adolescent-centred communication through a communication paper that allowed adolescents to electronically select topics they would like to discuss with HCPs (de Hosson et al, 2020) and posters highlighting developmentally appropriate steps for increased self-management (Kovacs et al, 2012).…”
Section: Intervention Characteristics Intervention Componentsmentioning
confidence: 99%
“…Goal setting was highlighted as a skill to supplement the knowledge that was disembarked through educational components (n =1, 10 %) (Krasuski & Maslow, 2020). Habibi et al, 2017;Kovacs et al, 2012). Activities within this component included transition events that included tours (n=2, 20%) and introductions with the adult care teams (n=2, 20%) (Habibi et al, 2017;Kovacs et al, 2012), reading materials with contact information (n=3, 30%) (Acuña Mora et al, 2017, 2020de Hosson et al, 2020;Kovacs et al, 2012) and understanding the transfer process (n=1, 10%) (Ladouceur et al, 2017).…”
Section: Skill Development Skill Development Components Included Acti...mentioning
confidence: 99%